2022
DOI: 10.1126/sciadv.abm8501
|View full text |Cite
|
Sign up to set email alerts
|

Translational recoding by chemical modification of non-AUG start codon ribonucleotide bases

Abstract: In contrast to prokaryotes wherein GUG and UUG are permissive start codons, initiation frequencies from non-AUG codons are generally low in eukaryotes, with CUG being considered as strongest. Here, we report that combined 5-cytosine methylation (5mC) and pseudouridylation (Ψ) of near-cognate non-AUG start codons convert GUG and UUG initiation strongly favored over CUG initiation in eukaryotic translation under a certain context. This prokaryotic-like preference is attributed to enhanced NUG initiation by Ψ in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Previous studies of duo-coding genes reported that the alternative product from POLG and RPL36 also used CTG and GTG instead of AUG as start codons for translation 28 . Translation initiation from non-AUG codons may involve canonical Kodak sequences 29 , internal ribosome entry sites 30 or chemical modification of codons 31 . This alternative translation initiation appears to have a preference for non-AUG codon-guided initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of duo-coding genes reported that the alternative product from POLG and RPL36 also used CTG and GTG instead of AUG as start codons for translation 28 . Translation initiation from non-AUG codons may involve canonical Kodak sequences 29 , internal ribosome entry sites 30 or chemical modification of codons 31 . This alternative translation initiation appears to have a preference for non-AUG codon-guided initiation.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these marks are enzymatically deposited in a site-specific manner affecting RNA stability, structure, RNA–RNA and RNA–protein interactions ( 10 ). During translation initiation, RNA modifications may guide the recruitment of ribosomes to the start codon, modulating the translation efficiency ( 11 , 12 ). The presence of RNA modifications also defines the secondary structure of the RNA molecule, having a direct impact on the accessibility to ribosomes and other initiation factors to the start codon ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%